Mascot Design as Brand Identity Communication Science Study Program UMSIDA - Febrillian, Kevin Wahyu; Aesthetika, Nur Maghfirah (Indonesian Journal of Cultural and Community Development, 2024)
General background: Mascots serve as effective visual identity elements for various organizations to convey character uniquely. Specific background: The Communication Science Study Program at Universitas Muhammadiyah Sidoarjo (UMSIDA) uses "Si Kombi," a character blending human and butterfly features, in colors representing the program's identity. Knowledge gap: Limited research exists on mascots' role in academic branding and public engagement. Aims: This study evaluates "Si Kombi" as a visual tool for building the program's brand and attracting interest. Results: The mascot’s design features two-dimensional elements with dominant colors, enhancing recognition and appeal among potential students. Novelty: Integrating a mascot into academic branding offers a fresh approach to promoting study programs. Implications: This study highlights how mascots can strengthen academic brands, enhance promotion, and foster emotional connections with audiences. Highlights: Brand Representation: "Si Kombi" serves as a unique visual identity for UMSIDA's Communication Science Study Program. Effective Engagement: The mascot enhances public attention, making the program more recognizable to prospective students. Innovative Strategy: Using mascots in academic branding adds a fresh approach to promotional efforts in educational institutions. Keywords: Mascot, Visual Identity, Branding, Academic Promotion